Pendampingan PAUD di TK Aisyiah Jetis Blulukan Colomadu Karanganyar - Eni Setyowati; Maulidyah Indira Hasmarini; Daryono Subagyo; Wuri Nur Indah Sari (Abdi Psikonomi, 2021)
Education for early childhood is the provision of efforts to stimulate, guide, nurture and provide learning activities that will produce children's abilities and skills. This service is carried out at Aisiyah Jetis Kindergarten located in Blulukan Village, Colomadu. The main problem of Aisyiah Kindergarten is the lack of socialization to local residents and the quality of education is not guaranteed so that many local residents do not send their children to the kindergarten, but choose schools outside the village. This activity resulted in a SWOT analysis of TK Aisyiah as follows: Strengths: TK Aisyah is located in a densely populated village, this is a source of strength for the school to acquire more students. Weaknesses: The school is located on the 2nd floor of the Al Huda Mosque so it makes parents less comfortable to send their children to the school. Opportunity: The school must show that the school is a quality school so that it can attract people to send their children to the kindergarten. Threats: The emergence of many new schools that provide facilities and comfort for students and parents.